RISK FACTORS FOR DUPLICATION OF NSAIDs WITHOUT GASTROPROTECTIVE IN ONE OF THE HOSPITALS IN INDONESIA - Nurmesa, Adi; Jannah, Wardatul; Rachman, Abu; Wahyudi (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
The use of dual NSAIDs without gastroprotective is one of the drug related problems that often occurs in hospitals, the purpose of giving dual NSAIDs is to increase the effectiveness of pain relief in reducing pain in patients. However, the use of dual NSAIDs without gastroprotective increases the risk of side effects on the gastrointestinal tract, kidneys, and cardiovascular system. This study aimed to examine the risk factors for duplication of NSAID therapy without gastroprotective in the outpatient pharmacy unit at a type C hospital in Banyuasin district. This analytical study used a cross-sectional research design to determine the influence of risk factors on the incidence of duplication of NSAIDs therapy without gastroprotective in the outpatient polyclinic. Data were analyzed using Pearson Chi Square analysis. The results of the bivariate analysis showed that older age, polypharmacy, and multipathology were factors associated with the incidence of NSAID duplication in outpatients with p values (OR) of 0.047 (1.101), 0.025 (2.63), 0.025 (2.63), and 0.025 (2.63), respectively. Keywords: Therapeutic duplications, Ibuprofen, Diclofenac, Gastroprotective agent